2007
DOI: 10.3892/or.18.6.1529
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase expression in high grade soft tissue sarcomas

Abstract: Abstract. Soft tissue sarcomas comprise a heterogeneous group of mesenchymal tumors with varying biological behavior ranging from indolent tumors with no or minimal metastatic risk to aggressive and frequently metastasizing tumors. Among the more common aggressive adult soft tissue sarcomas are malignant fibrous histiocytoma, synovial sarcoma and liposarcoma. Matrix metalloproteinases are enzymes which perform a homeostatic role in mesenchymal tissue and function in both tumorigenesis and metastasis. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In fact, CD147 expression has already been previously studied in a cohort of high grade soft tissue sarcomas, however, with no significant prognostic value [33]. In the present study, as the cohort also included low grade tumors, CD147 was significantly associated with high grade tumors.…”
Section: Discussionmentioning
confidence: 47%
“…In fact, CD147 expression has already been previously studied in a cohort of high grade soft tissue sarcomas, however, with no significant prognostic value [33]. In the present study, as the cohort also included low grade tumors, CD147 was significantly associated with high grade tumors.…”
Section: Discussionmentioning
confidence: 47%
“…The same is true for rs2071888 in TAPBP , a missense mutation. As noted above, several studies have observed over-expression of matrix metalloproteinase genes in GISTs and other soft tissue sarcomas [ 23 - 25 ], though none of the evaluated SNPs have previously been associated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The present report includes results from the second phase of the study, in which we examined the relationship between these 7 somatic mutation categories and 522 additional candidate SNPs. These SNPs are located on genes that play secondary or less well-understood roles in dioxin response or toxin-metabolizing pathways, as well as SNPs on PDGFRA and 10 matrix metalloproteinase ( MMP ) genes, which are often over-expressed in GISTs and other soft tissue sarcomas and may be linked to tumor invasion and metastasis [ 23 - 25 ]. Based on previous evidence that immune and inflammation-related genes are associated with osteosarcomas and other gastrointestinal tumors [ 26 - 28 ], we also selected certain SNPs from the GeneChip® Human Immune and Inflammation SNP Kit genotyping panel designed by Affymetrix® [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metalloproteinase inhibitor TIMP4 that was found to be the most downregulated gene has previously been associated with efficient tumor suppression in breast cancer cells [45] and its [46], a study that selectively focused on spindle-cell-like lesions could correlate higher MMP and lower TIMP expression to high-grade and malignant tumors [47]. Interestingly, all the genes identified as differentially regulated in the tumors that developed metastasis were downregulated compared to their expression in the tumors that did not seed distant lesions.…”
Section: Discussionmentioning
confidence: 99%